Exploring the Psychological Health and Work Efficiency of Enterprise Employees under the EAP Perspective - Wang, Liying; Shahnaz Sheibani (International Journal of Social Sciences and Public Administration, 2024)
Against the backdrop of rapid global economic advancement, intensifying corporate competition has made employee mental health a pivotal factor affecting both organizational performance and employee well-being. Employee Assistance Programs (EAPs), as structured mental health support services, have garnered increasing attention from corporate entities and academia alike. EAPs not only aim to address employees' psychological issues but also strive to enhance their work efficiency and overall satisfaction. By offering psychological counseling, stress management, and other comprehensive services, EAPs effectively alleviate workplace stress, promote mental well-being, and consequently elevate corporate productivity and competitiveness. Research underscores a significant positive correlation between mental health and work efficiency. Maintaining a healthy psychological state facilitates sustained high performance among employees, mitigating absenteeism and turnover stemming from psychological issues. As businesses increasingly prioritize employee mental health, the global adoption of EAPs is becoming more widespread. However, enterprises face various challenges in implementation, such as safeguarding employee privacy, low participation rates, and resource constraints. Thus, exploring the impact of EAPs on employee mental health and work efficiency, analyzing challenges encountered during implementation, and devising corresponding strategies are crucial for optimizing management practices and enhancing operational efficiency in enterprises.